Contrasting physical and biochemical properties of orchard soils suppressive and conducive to Fusarium wilt of banana. (20th December 2017) - Li, Z.; Deng, Z.; Chen, S.; Yang, H.; Zheng, Y.; Dai, L.; Zhang, F.; Wang, S.; Hu, Shuijin
Abstract: Fusarium wilt disease is one of the most serious soil‐borne diseases in banana orchards worldwide. Some soils are suppressive to Fusarium wilt, although the mechanisms are still unclear. In this study, two typical banana‐growing soils (ultisol and inceptisol), which were either suppressive or conducive to Fusarium wilt, were collected from Hainan, China. Particle size distribution, pH values, electrical conductivity (EC), enzyme activities and microbial polymerase chain reaction amplification of the soil samples were analysed. The suppressive soils had significantly more >2 and <0.053 mm aggregates than the conducive soils. In addition, the suppressive soils had a comparatively even size distribution within the range of 0–0.25 mm. Total carbon, total nitrogen and soil enzyme activities in the aggregates of suppressive soils were also significantly higher than those in the conducive soils. For example, soil invertase activities in the >2 mm aggregates were 7.9–11.9 and 3.2–3.3 mg/g for the suppressive and conducive soils, respectively. Furthermore, in situ EC can be applied as an indicator of the integrated contrast between the suppressive and conducive soils, and could be a new tool for monitoring soil‐borne disease.